Microhardness change of enamel due to bleaching with in-office bleaching gels of different acidity - Magalhaes, Juliana G. [UNESP]; Marimoto, Angela R. K. [UNESP]; Torres, Carlos R. G. [UNESP]; Pagani, Clovis [UNESP]; Teixeira, Symone C. [UNESP]; Barcellos, Daphne C. [UNESP] (Informa Healthcare, 2012)
Objective. The aim of this study was to assess the enamel microhardness treated with three in-office bleaching agents, containing 35% hydrogen peroxide with different acidity. Materials and methods. Bovine incisors were divided into three groups that received the following bleaching agents: Whiteness HP, Total Bleach and Opalescence Xtra. Three gel applications/10-min each, totaling 30-min of bleaching treatment, were made on the teeth and activated with a blue LED (1000 mW/470 nm) combined to a LASER (120 mW/795 nm) device (Easy Bleach-Clean Line). Vickers hardness (VH) was evaluated at baseline and after the bleaching procedure. The values of Hardness loss [HNL] (% reduction) were calculated. The two-sample t-test was used for comparison of the HNL of the three bleaching products (5% level of significance). Results. The Opalescence Xtra, which had the lowest pH value (pH = 4.30), showed a significant increase of HNL when compared with Total Bleach bleaching agent, which had the highest pH value (pH = 6.62). Conclusions. The 35% hydrogen peroxide bleaching agents resulted in a reduction in surface enamel microhardness and bleaching with the most acid agent resulted in a significant enamel hardness loss compared to the less acid agent (4.30 vs 6.62). Strategies proposed to reduce the enamel loss after bleaching treatment may include the use of daily fluoride therapy, mouth rinsing (fluoride, milk and sodium bicarbonate solution), fluoride/bicarbonate dentifrices without abrasives, do not toothbrush immediately after bleaching, fluorides and calcium add to bleaching agents.
Keywords: bleaching; enamel; hydrogen peroxide; microhardness; pH